2013
DOI: 10.1111/corg.12039
|View full text |Cite
|
Sign up to set email alerts
|

Do Responsible Investment Indices Improve Corporate Social Responsibility? FTSE4Good's Impact on Environmental Management

Abstract: Manuscript Type: EmpiricalResearch Question/Issue: This study investigates the impact of a responsible investment index on environmental management practices. Firms that were included in the FTSE4Good index but failed to meet enhanced requirements were subject to both engagement by FTSE and the threat of expulsion from the index. We examine the combined effect of these actions, estimate the contribution of both elements separately, and the influence of concentrated equity ownership, corporate governance, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 68 publications
(124 reference statements)
3
40
1
Order By: Relevance
“…Twice a year the FTSE4Good Policy Committee convenes to review the Index CSP criteria and include or exclude companies. The FTSE4Good Index has the dual objective to serve investors interested in RI, and to incentivise companies to improve their CSP through raising the bar for Index inclusion (FTSE, 2010;Slager et al, 2012;Mackenzie, Rees, & Rodionova, 2013). Additional inclusion criteria have been introduced throughout the years since the Index was launched, on topics as diverse as climate change, supply chain labour standards and anti-bribery practices.…”
Section: Methodsmentioning
confidence: 99%
“…Twice a year the FTSE4Good Policy Committee convenes to review the Index CSP criteria and include or exclude companies. The FTSE4Good Index has the dual objective to serve investors interested in RI, and to incentivise companies to improve their CSP through raising the bar for Index inclusion (FTSE, 2010;Slager et al, 2012;Mackenzie, Rees, & Rodionova, 2013). Additional inclusion criteria have been introduced throughout the years since the Index was launched, on topics as diverse as climate change, supply chain labour standards and anti-bribery practices.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, ESG rating agencies have emerged as relevant market actors for CSP assessment and, consequently, for companies' management. Only a few previous studies have analyzed the relationship between ESG rating agencies and corporate sustainability practices (Collison et al, 2009;Mackenzie et al, 2013;Slager, 2015); however, the results are inconclusive. However, little research has been done on whether raters measure corporate sustainability accurately and how they do it (Delmas, Etzion, & Nairn-Birch, 2013;Escrig-Olmedo, Muñoz-Torres, & Fernandez-Izquierdo, 2010).…”
Section: "Process"-how Is It Measured? Esg Rating Agenciesmentioning
confidence: 99%
“…Although knowledge is limited on how ESG rating agencies and indices are used within companies to produce organizational change (Slager, 2015), several studies show that sustainability index membership influences the behavior of companies (Collison, Cobb, Power, & Stevenson, 2009;Mackenzie, Rees, & Rodionova, 2013;Pätäri, Jantunen, Kyläheiko, & Sandström, 2012). Although knowledge is limited on how ESG rating agencies and indices are used within companies to produce organizational change (Slager, 2015), several studies show that sustainability index membership influences the behavior of companies (Collison, Cobb, Power, & Stevenson, 2009;Mackenzie, Rees, & Rodionova, 2013;Pätäri, Jantunen, Kyläheiko, & Sandström, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Williams and Crawford (2011) analyzed how S&P 500 firms choose to influence climate change policy and indicated that those firms tend to adopt constituency-building rather than financial incentive tactics. Mackenzie et al (2013) examined the impacts of a responsible investment index on environment management practices. Rehbein and Logsdon (2013) investigated how corporations respond to social-policy related shareholder resolutions and noted that corporate managers are more likely to communicate with shareholder activists when the firms are larger and have a lower percentage of institutional investors.…”
Section: Shareholder Activism In Csr and Climate Changementioning
confidence: 99%